Indirect effect of alpha-1-antitrypsin on endotoxin-induced IL-1β secretion from human PBMCs - Janciauskiene, Sabina; Tumpara, Srinu; Schebb, Nils Helge; Buettner, Falk F. R.; Mainka, Malwina; Sivaraman, Kokilavani; Immenschuh, Stephan; Grau, Veronika; Welte, Tobias; Olejnicka, Beata (Frontiers in Pharmacology, 2022)
Human alpha1-antitrypsin (AAT) encoded by the SERPINA1 gene, is an acute phase glycoprotein that regulates inflammatory responses via both protease inhibitory and non-inhibitory activities. We previously reported that AAT controls ATP-induced IL-1β release from human mononuclear cells by stimulating the release of small bioactive molecules. In the current study, we aimed to elucidate the identity of these putative effectors released from human PBMCs in response to AAT, which may inhibit the LPS-induced release of IL-1β. We pre-incubated human PBMCs alone or with different preparations of AAT (4 mg/ml) for 30 min at 37C, 5% CO2, and collected cell supernatants filtered through centrifugal filters (cutoff 3 kDa) to eliminate AAT and other high molecular weight substances. Supernatants passed through the filters were used to culture PBMCs isolated from the autologous or heterologous donors with or without adding LPS (1 µg/ml) for 6 hours. Unexpectedly, supernatants from PBMCs pre-incubated with AAT (Zemaira), but not with other AAT preparations tested or with oxidized AAT (Zemaira), lowered the LPS-induced release of IL-1β by about 25-60% without affecting IL1B mRNA. The reversed-phase liquid chromatography coupled with mass spectrometry did not confirm the hypothesis that small pro-resolving lipid mediators released from PBMCs after exposure to AAT (Zemaira) are responsible for lowering the LPS-induced IL-1β release. Distinctively from other AAT preparations, AAT (Zemaira) and supernatants from PBMCs pre-treated with this protein contained high levels of total thiols. In line, mass spectrometry analysis revealed that AAT (Zemaira) protein contains freer Cys232 than AAT (Prolastin®). Our data show that a free Cys232 in AAT is required for controlling LPS-induced IL-1β release from human PBMCs. Further studies characterizing AAT preparations used to treat patients with inherited AAT deficiency remain of clinical importance.